Comparison of efficacy of silver-nanoparticle gel, nano-silver-foam and collagen dressings in treatment of partial thickness burn wounds. Issue 8 (December 2019) - Erring, Miying; Gaba, Sunil; Mohsina, Subair; Tripathy, Satyaswarup; Sharma, Ramesh Kumar
Highlights: Faster healing rates were found in silver-foam group than collagen and silver gel. Time taken and ease of application was better with silver foam dressings. Earlier reduction in pain scores was noted with silver foam dressings. The scar quality, cost and infection rates were similar between three groups. Nanosilver foam dressings were more efficacious in partial thickness burns. Abstract: Introduction: This study was carried out to compare the efficacy of silver nanoparticle gel (SG), nanosilver foam (SF) and collagen (C) dressings in partial thickness burn wounds. Methods: This was a single-center, prospective cohort study carried out over a period of 1 year on patients with 15–40% partial thickness thermal burns ≤48 h. Each patient received all three dressings (silver-nanoparticle gel, nanosilver foam, collagen) simultaneously at 3 randomly selected areas which were comparable in terms of burn depth and surface area. Efficacy of the dressings was assessed in terms of healing rates, time taken and ease of application, pain at dressing change, cost, wound-swab culture and scar quality (at 3 months). Results: A total of 20 patients were included. In SF group, number of patients with 60%–80% re-epithelialization on day10 (SG: 10/20; C: 10/20; SF: 16/20; p = 0.042) and complete healing on day14 (SF: 11/20, C: 6/20, SG: 4/20; p = 0.032) was significantly higher. The time for dressing change was similar at admission (p = 0.918) and day 10 (p = 0.163), although majority of the patients in SF group needed less than 10 min. The time taken (<10 min) was significantly lower in SF group by 14th day (SF: 18/20 C: 6/20 SG: 6/20; p < 0.001). The ease of application rated by clinicians as "extremely easy" was significantly better in SF group (SG: 78%, C: 80%, SF: 95%; p = 0.011). There was a significantly faster decrease in pain scores in SF group by 5th day (VAS score SF: 6, C: 8; SG: 8; p = 0.038), however, pain scores were comparable at 2 weeks. The scar quality (p = 0.82), cost (p = 0.09) and infection rates (SG: 7/20; C: 4/20; SF: 3/20; p = 0.05) were comparable. The need for skin-graft cover was lower in SF group (SG: 5/20; C: 3/20; SF: 1/20). Conclusion: Nanosilver-foam dressings were found to be more efficacious for re-epithelialization, healing, ease of application, tolerance when compared to silver nanoparticle gel and collagen dressings in partial-thickness burns. All were found to be safe.